Developing Malang City Tourism: A Qualitative Analysis of Opportunities, Challenges, and Sustainability Strategies - Iswari, Hanif Rani; Baits Nur, Ayu Wandani Mustika Rahma; Rusdianti, Imanita Septian (PANGRIPTA, 2025)
Malang City possesses diverse tourism potential, ranging from thematic villages, culinary and educational tourism, to emerging halal tourism destinations. However, the city is often perceived merely as a transit point for visitors heading to Batu or Mount Bromo, limiting its positioning as a primary destination. This study aims to analyze tourism development strategies for Malang City using a qualitative descriptive approach supported by primary and secondary data. Primary data were collected through in-depth interviews with thematic village managers, culinary business owners, and representatives of the Malang City Tourism Office, while secondary data were drawn from statistical reports and scholarly literature. Findings reveal that Malang’s tourism development can be strengthened through five key strategies: differentiation of attractions (creative, culinary, and halal tourism), improvement of infrastructure and public facilities, multi-stakeholder collaboration, empowerment of local communities, and digital promotion. The study highlights that sustainable and inclusive planning is critical for transforming Malang from a mere stopover into a leading tourism destination in East Java, with broader socio-economic benefits for local communities.